Research on restraint strategies for rearward-reclined occupants in a frontal rigid barrier crash - Daowen Zhang; Jixiang Yang; Yi Lei; Junlian Yan; Lei Xu (Scientific Reports)
Abstract Autonomous driving technology has led to an increasing preference for rearward seating postures. However, current restraint systems exhibit significant shortcomings in protecting reclined occupants. In this paper, based on the existing restraint system components, various restraint strategies were configured to enhance the protection for reclined occupants. Firstly, this research developed a model of the driver-side restraint system and validated its accuracy; secondly, it analyzed the kinematic response and damage of the occupants with the protection of the conventional restraint system; and then, based on the characteristics of the occupant’s kinematic response, it put forward three kinds of restraint strategies. The results indicated that incorporating larger airbags and additional knee bolsters could significantly enhance the protective effectiveness of the restraint system. This strategy achieved reduction of 18.9% in HIC15ms, 2.6% in maximum stress on the cervical spine, 17% in maximum chest compression, 4% in maximum rib strain, and 21% in axial force on the legs. The research findings offer valuable insights for the future design of protection systems for reclined occupants.